High-entropy (Ca0.2Sr0.2Ba0.2La0.2Pb0.2)TiO3 perovskite ceramics with A-site short-range disorder for thermoelectric applications. (20th January 2022) - Zhang, Ping; Lou, Zhihao; Qin, Mengjie; Xu, Jie; Zhu, Jiatong; Shi, Zongmo; Chen, Qian; Reece, Michael J.; Yan, Haixue; Gao, Feng
Highlights: High-entropy (Ca0.2 Sr0.2 Ba0.2 La0.2 Pb0.2 )TiO3 thermoelectric ceramic was prepared. Low κ of 1.75 W/mK and high | S | of 272 μV/K at 1073 K were reported. Long-range structural order and short-range chemical disorder lead to suppression κ . Pave a way of effectively reducing κ through high-entropy engineering to improve ZT . Abstract: Novel high-entropy perovskite-type (Ca0.2 Sr0.2 Ba0.2 La0.2 Pb0.2 )TiO3 (CSBLP) ceramics with cubic structure of Pm-3m space group were successful prepared by solid-state reaction method. Results of XRD, SEM-EDS, HRTEM confirmed a homogeneous distribution and equimolar arrangement of multicomponent cations on the A-site. The high-entropy CSBLP ceramics showed long-range structural order and short-range chemical disorder with widely dispersed nanoscale grains varying sizes of 4-6 nm in the microstructure. Because of increased configurational entropy, the CSBLP ceramic has an enhanced Seebeck coefficient ( | S | = 272 μV/K at 1073 K) and low thermal conductivity ( κ =1.75 W/mK at 1073 K) when annealed at 1300 °C. This work demonstrates the possibility of effectively reducing thermal conductivity and improving the performance of thermoelectric oxides through high-entropy composition design. Graphical abstract: Image, graphical abstract